Da escrita ideográfica aos emoticons: um estudo à luz da historiografia linguística - Silva, Marcelo da (2011)
This study sought to establish relations between the emoticons used in chat text and figures determinative of cuneiform and hieroglyphic, through the linguistic historiography, which (re) constructs the linguistic knowledge, identifying their context and their influence in producing the document, in a particular historical time and geographical space. When we make a historical overview of writing, we rescued the main features of ideographic writing of the Sumerians and Egyptians with their signals determinative that served to help readers understand the meanings of texts and also to avoid possible ambiguities. Historically, the writing of Semitic, Greek and Roman, was instrumental in shaping our current alphabet. At the end of the twentieth century and beginning of the XXI came the Internet as a communication vehicle that offers new ways of relating to chat in an open space for interaction in digital media. Thus, this research found that there are both similarities and differences between the emoticons used in chat rooms and signals determinative of the Sumerians and Egyptians. As for similarities, both have ideographic value, or transmit ideas and words with accompanying phonetic value. While the determinative signs were intended to help the reader in understanding the words, emoticons have the role to complement the written message